2016
DOI: 10.1039/c6nr02493a
|View full text |Cite
|
Sign up to set email alerts
|

Solution-based intramolecular singlet fission in cross-conjugated pentacene dimers

Abstract: aWe show unambiguous and compelling evidence by means of pump-probe experiments, which are complemented by calculations using ab initio multireference perturbation theory, for intramolecular singlet fission (SF) within two synthetically tailored pentacene dimers with cross-conjugation, namely XC1 and XC2. The two pentacene dimers differ in terms of electronic interactions as evidenced by perturbation of the ground state absorption spectra stemming from stronger through-bond contributions in XC1 as confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
156
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 115 publications
(169 citation statements)
references
References 80 publications
11
156
0
2
Order By: Relevance
“…The S 1 lifetime is systematically shortened with increasing polarity, from 1.17 ps in hexane to ∼300 fs in the most polar solvents. As previously noted812, this direct correlation of SF time constant to solvent polarity suggests triplet formation is mediated by CT states, though these are not directly resolved. However, we highlight the intriguing spectral shape of S 1 in the NIR.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…The S 1 lifetime is systematically shortened with increasing polarity, from 1.17 ps in hexane to ∼300 fs in the most polar solvents. As previously noted812, this direct correlation of SF time constant to solvent polarity suggests triplet formation is mediated by CT states, though these are not directly resolved. However, we highlight the intriguing spectral shape of S 1 in the NIR.…”
Section: Resultsmentioning
confidence: 58%
“…To circumvent these difficulties, recent efforts have focused on intramolecular SF in covalent dimers, most notably in various dimers of pentacene89101112. These materials provide uniquely detailed insight into the SF mechanism, particularly with regard to the influence of molecular geometry and charge-transfer (CT) states.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These are the singlet ground state |S 0 S 0 〉, the correlated triplet pair (or multi-exciton) state | 1 (T 1 T 1 )〉, the locally excited singlet states | 1 (S 1 S 0 )〉 and | 1 (S 0 S 1 )〉 and the CT states | 1 (CA)〉 and | 1 (AC)〉 (refs 2, 3, 26, 34). To assess the relevance of the different SF mechanisms, we have calculated the effective coupling, V eff , of | 1 (S 1 S 0 )〉 to | 1 (T 1 T 1 )〉 (or | 1 (S 0 S 1 )〉 to | 1 (T 1 T 1 )〉)3536:…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been hypothesized that the electronic coupling between the pentacenes is critical to render CT-state-mediated SF energetically accessible. While no evidence for CT-mediated SF was observed in pentacene dimers linked directly or using p -phenylene oligomers2425, work on π-conjugated and cross-conjugated pentacene dimers2627 has shown that effective π-conjugation enables fast, CT-state-mediated SF.…”
mentioning
confidence: 99%